2021
DOI: 10.30939/ijastech..923917
|View full text |Cite
|
Sign up to set email alerts
|

An URANS Simulation of the Kelvin-Helmholtz Aerodynamic Effect over the Ahmed Body

Abstract: The reduction of energy consumption of cars is always a significant issue in automotive design. Turbulent flow around a car body is very difficult to simulate accurately due to the complexity of the flow conditions around the body, such as complex flow separation and laminar to turbulent flow transition. In particular, flow over the Ahmed body with a rear angle of 25o is considered a challenging problem for the RANS approach with two-equation turbulence models. In this study, we aim to analyze the Kelvin-Helmh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…As a result, Both LES and DES have very high computation costs, which hinders the practical application of DES and LES for high Reynolds number flows around Ahmed Body [13] for ADO. It is also noteworthy that Igali et al [5] and Sadykov et al [8] showed that the RANS and URANS models could generate time-averaged results that are comparable to those of LES. This is a challenge to the established assumption that the LES/DES is always superior to the more efficient RANS/URANS approaches if the detailed resolution of the turbulent eddies is not required in engineering design.…”
Section: Literature Reviewmentioning
confidence: 95%
See 4 more Smart Citations
“…As a result, Both LES and DES have very high computation costs, which hinders the practical application of DES and LES for high Reynolds number flows around Ahmed Body [13] for ADO. It is also noteworthy that Igali et al [5] and Sadykov et al [8] showed that the RANS and URANS models could generate time-averaged results that are comparable to those of LES. This is a challenge to the established assumption that the LES/DES is always superior to the more efficient RANS/URANS approaches if the detailed resolution of the turbulent eddies is not required in engineering design.…”
Section: Literature Reviewmentioning
confidence: 95%
“…There are many published studies in the literature that present the results of simulations aimed to provide insight into the flow around the Ahmed body. For example, two recent studies showed the wake structures of the vehicle in detail by Igali et al [5] and Sadykov et al [8], respectively, with the former using the RANS approach and the latter the URANS one. Their usefulness is in the comparison of results obtained by the RANS and URANS approaches with different turbulence models, where Igali et al [5] achieved 2.474% of error in comparison with experimentally measured drag coefficient using the RANS approach, while Sadykov et al [8] obtained 1.68% error using the URANS method.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations